Assessing the Bering-Chukchi-Beaufort Seas stock of bowhead whales using abundance data together with data on length or age - Punt, Andre E. (J. Cetacean Res. Manage., 2023)
The 1998 assessment of the Bering-Chukchi-Beaufort (B-C-B) Seas stock of bowhead whales (Balaena mysticetus) was conducted using a Bayesian estimation framework. That assessment ignored information on the length-frequency and age-composition of the harvests and the detailed length-frequency information from photogrammetry studies. The modelling framework used to assess the B-C-B Seas bowhead whales is therefore extended to make use of these data. The results indicate that selectivity is not uniform, as assumed in previous assessments, but rather domed-shaped, with young animals most vulnerable to harvest. The length-frequency, proportion, age-composition and abundance data are inconsistent to some extent. Fitting the model to the age-composition data leads to the most pessimistic estimates of stock status and productivity. The results of projections based on these assessments in which strike limits are set using the Bowhead Strike Limit Algorithm (SLA) suggest that none of the data sets are such that the scenarios considered when testing the Bowhead SLA should now be considered implausible.